Enam sigma dalam pengurusan makmal komputer di IPT: suatu cadangan - Hairulliza Mohamad Judi,; Siti Fairuz Yusof ,; Mohd Faiz Yahaya, (Penerbit ukm, 2008)

(untitled)
The Six Sigma approach which has been widely applied in the manufacturing sector has contributed to significant changes in reducing the number of defects. As a result, it has attracted many practitioners including those from the service industry to implement the strategy in their operations. This study aims at providing a prospect for implementing Six Sigma in computer laboratory management at Higher Learning Institution (HLI). Six Sigma approach has been selected not only to improve the service but also to handle critical problems in the process. Among the main challenges faced by the computer lab management team include continuous virus infection, network interruption, overheating, and hardware and software maintenance. The study considers the management of computer laboratory for two cases, i.e. the in Faculty of Information Sciences and Technology (FTSM) in UKM, and the Faculty of Design and Architecture (FRSB) in UPM. The proposed strategy for implementation of Six Sigma would serve as a guideline for the management team to apply the tool in their operations